Burden of family members in caring for senile dementia patients: an integrative review (Research, Society and Development, 2020)
Introduction: Population aging is a worldwide event, visible both in developed and developing countries. In Brazil, the number of elderly people is around 21 million. In 2025 Brazil is expected to be the sixth country in the world with the highest rate of elderly among its inhabitants. Objective: To verify the existence of overload to family members in the care of patients with senile dementia. Materials and methods: This is a research carried out through a literature review with a qualitative approach. The descriptors that guided the research were: dementia; caregivers; old man. Results: The main results obtained were that the caregivers suffer an extreme burden because the care, in addition to being centered on a single family member, is responsible in addition to excessive care for the elderly, management of domestic and financial activities, so the caregiver ends up being exhausted , because there is a total change in the life of this caregiver, where he finds himself trapped at home taking care of the sick. As a result, caregivers end up with a mix of negative and positive signs and symptoms. As negative signs and symptoms we have: emotional exhaustion, stress, anguish, physical exhaustion, impotence, guilt, depressive conditions, fear, despair and worry. And as positive signs and symptoms we have: love, relief, attention, solidarity, patience, dedication. Conclusion: Caregivers need to be included in education and support programs, to work on this burden, and to the maximum, try to reduce it effectively, so that it is not just a patient taking care of another patient.